Pengaruh Loan To Deposit Ratio, Net Profit Margin Dan Debt To Equity Ratio Terhadap Harga Saham PT Bank Mega Tbk Periode 2015-2023 - Shilfi Nahrisyah Ratu Sari Ramadan; Rudi Sanjaya (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This researcher aims to determine the influence of the Loan to Deposit Ratio, Net Profit Margin and Debt to Equity Ratio on the Share Price of PT Bank Mega Tbk for the 2015-2023 period partially or simultaneously. The research method for the type of data used is quantitative descriptive and secondary data, while the sample in this research is the financial report in the form of the balance sheet and profit and loss of PT Bank Mega Tbk for the 2015-2023 period. The data analysis method used is the classical assumption test and linear regression. Next, hypothesis testing uses the t test, f test and coefficient of determination. The results of this research show that the Loan to Deposit Ratio (LDR) partially influences the share price of PT Bank Mega Tbk for the 2015-2023 period as evidenced by the significance value of the Loan to Deposit Ratio variable of 0.023. Net Profit Margin (NPM) partially has no effect on the Share Price of PT Bank Mega Tbk for the 2015-2023 period as evidenced by the significance value of the Net Profit Margin variable of 0.314. Debt to Equity Ratio (DER) partially has no effect on the share price of PT Bank Mega Tbk for the 2015-2023 period as evidenced by the significance value of the Debt to Equity Ratio variable of 0.238. Loan to Deposit Ratio (LDR), Net Profit Margin (NPM) and Debt to Equity Ratio (DER) simultaneously influence the share price of PT Bank Mega Tbk for the 2015-2023 period as evidenced by the significance value of the Loan to Deposit Ratio (LDR) variable. Net Profit Margin (NPM) and Debt to Equity Ratio (DER) are 0.025.